A novel reliability-based high performance decoding algorithm for short block length turbo codes. (6th April 2020) - Salija, P.; Yamuna, B.; Padmanabhan, T.R.; Mishra, Deepak
Satellite communication applications use turbo codes as the standard error correcting code due to its Shannon's capacity approaching performance. However, short block length turbo codes exhibit significant performance degradation. This is a limiting factor in applications like transmissions over the telecommand links for satellite communications that involve the use of short length turbo codes. A novel reliability-based turbo decoding algorithm that addresses the performance improvement of short block length turbo codes, is being proposed in this paper. Simulation results show a coding gain of 2.45 dB at BER of 10 −3 for short length codewords. The proposed decoding algorithm has low computational complexity compared to the conventional iterative decoding algorithm. The relatively lower computational complexity and the conspicuous improvement in BER performance make the method quite attractive.